Virtual treasure hunt: a gamification approach of learning Arabic Language among AFL learners - Mohamad Helni, Mohamad Ikmal Hakimi; Ghazali, Najihah (2022)
Foreign language learners sometimes find it hard to learn the language as they often confront unfamiliar vocabularies which eventually result in difficulty to understand and comprehend the language. Consequently, learners who are still on their elementary levels in learning Arabic language find this a burden which invariably leads them to have less interest in learning the language. Many researchers suggested that a more fun, engaging approach must be adopted to learning foreign language. Studies have shown that one of the ways to achieve this approach is by applying gamification elements in the learning process. Therefore, this research focuses on a gamification approach to learning Arabic language by implementing task-based activities through Virtual Treasure Hunt (VTH). This VTH includes suitable topics in Arabic that suit the need of elementary AFL learners which are divided into three stages that cover all four language skills through easily accessible online platforms. This research aims to assess learner's vocabulary mastery at the elementary level which will then help in developing four language skills as well as to deliver such knowledge through a more fun, engaging gamified method. This VTH is currently still in its trial phase which will be released as an application in the future and will contribute more to the acquisition of Arabic language among learners. Hence, it is believed that this gamified language learning approach will help learners grasp the language and understand them well.